GE_GERICHTE A/3764/2023 vom 20. Mai 2025 - GE Cour de justice (2025)
IMPÔT;IMPÔT CANTONAL ET COMMUNAL;IMPÔT FÉDÉRAL DIRECT;PRESCRIPTION;SOUSTRACTION D'IMPÔT;TENTATIVE(DROIT PÉNAL);FIXATION DE L'AMENDE;NE BIS IN IDEM | LIFD.175.al1; LIFD.175.al2; LPFisc.69.al1; LPFisc.69.al2